Addis Test in Brucellosis - Célis Gutiérrez, Eduardo Fausto (1965)
In 1925 Thomas Addis, ( 17) , (2 ) , first made the study of normal and abnormal urinary sediment. This test proved to be of great importance for the diagnosis of kidney disease. Since its inception in San Francisco , USA. UU . , Its application in clinical practice quickly spread to everyone and found its usefulness, particularly in the diagnosis and control of the development and the effectiveness of therapy in nephritis . Addis technique for its simplicity and easy interpretation has become a very common test in all clinical laboratories. We have tried to make changes, but have not been more welcome. Goldring 9) , Jiménez Díaz ( 12) , Kolmer (13 ) Lyttle (17 ) , Boyle ( 3) and many other high quality researchers have done studies that proved the importance of the test and considered as an indirect biopsy renal parenchyma . In 1937 Manrique Vitaliano (17 ) , between us , for the first time applied and demonstrates the diagnostic utility and evolving in the course of renal disease in patients of " Dos de Mayo " Hospital. Since then , examination of the urinary sediment is rule making in patients with kidney infections.